Penerapan Model Pembelajaran Problem Based Learning (PBL) dengan Media Permainan Undian untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa SMP pada Materi Pola Bilangan - Syumneri Syumneri; Syarifah Fadillah; Reni Astuti (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the application of problem based learning learning models with lottery game media in improving junior high school students' problem solving abilities. This research is an experimental research in the form of Pre-Experimental Designs. The design used is One Group Pretest-Postest Design. The population in this study were class VIII A and class VIII B. The sample in this study was students of class VIII B consisting of 20 students with the selection of subjects based on the cluster random sampling technique. The data collection technique used is a measurement technique with a data collection tool in the form of test questions in essay form. The data analysis technique used was anava one line of dissimilar cells, with further testing using the Scheffe method. The research results obtained were that there was a significant increase in students' mathematical problem solving abilities before and after being given treatment through the problem based learning model using lottery media with high categories.